A thermo-viscoelastic model of process-induced residual stresses in composite structures with considering thermal dependence. (February 2016) - Ding, Anxin; Li, Shuxin; Sun, Jiuxiao; Wang, Jihui; Zu, Lei
Abstract: A more general formulation of a thermo-viscoelastic law which considers the thermal dependence on residual stresses during curing or post curing is proposed. The formulation has not been captured before by earlier presented models by Zocher et al. [35] and Jun et al. [34] which are special cases of the more general formulation. In the proposed model the residual stresses development of thermo-rheologically complex materials could be carried out, and the changes in thermal expansion, chemical shrinkage and stresses relaxation are taken into account. The proposed model containing the thermal dependence and its corresponding finite element code incorporated into ABAQUS with UMAT subroutine was numerically validated by comparison to two illustrative examples. Furthermore, the effects of thermal dependence on the residual stresses and distortions in the composite structures were evaluated. The results reveal that the residual stresses and distortions in composite structures exhibit significant reduction with considering the thermal dependence.